The Effect of Characteristic CEO and Innovation on Tax Avoidance - Dewi, R.Rosiyana; Suryoyudanto, Mahaji; Atsil Vinandra, Farras (Universitas Trisakti, 2023)
This study aims to examine the influence of CEO characteristics consisting of CEO overconfidence, CEO compensation, CEO attributes, and innovation towards tax avoidance. The population in this study is a company listed on the Indonesia Stock Exchange in the primary consumer sector for the 2017-2021 period using the purposive sampling method, which obtained 165 samples. This research is classified as a quantitative research conducted to test the hypothesis. The test results in this study accept three of the six hypotheses proposed. Variables CEO tenure, and innovation have a positive effect on tax avoidance. Meanwhile, CEO overconfidence, CEO compensation, and CEO age have no effect on tax avoidance.